Training methods that improve MD–PhD student self-efficacy for clinical research skills - Sebastian, Mathew; Robinson, Matthew A.; Dumeny, Leanne; Dyson, Kyle A.; Fantone, Joseph C.; McCormack, Wayne T.; Stratford May, W. (Journal of clinical and translational science, 2019)
MD-PhD training programs train physician-scientists to pursue careers involving both clinical care and research, but decreasing numbers of physician-scientists stay engaged in clinical research. We sought to identify current clinical research training methods utilized by MD-PhD programs and to assess how effective they are in promoting self-efficacy for clinical research. The US MD-PhD students were surveyed in April-May 2018. Students identified the clinical research training methods they participated in, and self-efficacy in clinical research was determined using a modified 12-item Clinical Research Appraisal Inventory. Responses were received from 61 of 108 MD-PhD institutions. Responses were obtained from 647 MD-PhD students in all years of training. The primary methods of clinical research training included no clinical research training, and various combinations of didactics, mentored clinical research, and a clinical research practicum. Students with didactics plus mentored clinical research had similar self-efficacy as those with didactics plus clinical research practicum. Training activities that differentiated students who did and did not have the clinical research practicum experience and were associated with higher self-efficacy included exposure to Institutional Review Boards and participation in human subject recruitment. A clinical research practicum was found to be an effective option for MD-PhD students conducting basic science research to gain experience in clinical research skills. Clinical research self-efficacy was correlated with the amount of clinical research training and specific clinical research tasks, which may inform curriculum development for a variety of clinical and translational research training programs, for example, MD-PhD, TL1, and KL2.